Исследование сопротивления усталости ЦАПФ задних мостов специальных транспортных средств - Лобанов, Виктор Константинович; Пашкова, Галина Ивановна (НТУ "ХПИ", 2014)
В работе выполнено исследование сопротивления усталости цапф заднего моста транспортного средства «Дозор» различных вариантов изготовления. Показано, что оптимальными являются испытания деталей при совместном действии изгиба и кручения. Установлено, что место соединения цапфы с насадкой является менее нагруженным и напряженным, чем шлицы и зона крепления цапфы к корпусу.

The study is related to the development of the special vehicle "Dozor". This work presents the researching of the fatigue resistance of rear axles trunnions for the vehicle "Dozor" from different variants of manufacturing. Totally, 20 different constructions of the trunnion, namely welded (11 variants) and mixed (9 variants) ones are examined. Universal testing machine, enabling to generate maximum static load of 500 kN and maximum cyclic load of 250 kN with an accuracy of ± 1% is used for testing. Working load is simulated using loading conditions. It is shown that the test items are optimal under the combined action of bending and torsion. Examples of the tensometry results and final results of all tests are given. It was founded that the connection point of trunnion with nozzle is less loaded and less stressful than splines and zone, where trunnion is connected to the body. Approved test pattern for trunnion under the simultaneous action of the bending and torsional moments is recommended for further use in the development of technologies and standards in percentage check tests of trunnions in serial production for the purpose of intermittent monitoring of the level and stability of the quality of their manufacture.
Keywords: машиностроение; эксплуатационная надежность; быстроходные двигатели; методика испытаний; изгиб; кручение; тензометрирование